Calculated Ocean Tides in Gili Air harbour (Lombok, Indonesia) from March to June 2020 - Jarrid Tschaikowski (PANGAEA, 2020)
Measured pressure and calculated tides at the harbour of Gili Air (Lombok, Indonesia) is presented. The data was collected during the fieldwork for a Master Thesis (Hydrogeology, University Bremen) in cooperation with the Leibniz Centre for Tropical Marine Research between March and June 2020.